Burnout in COVID-19 era - a literature review - Magdalena Leśniewska; Ilona Kozioł; Julia Budzyńska; Joanna Milanowska (Kazimierz Wielki University, 2021)
BACKGROUND:  The COVID-19 pandemic brought changes to daily life of many people. One of those affected by the global pandemic arena was work life. One of the results is burnout due to new challenges and stress associated with them. The most exposed occupational group were healthcare workers as the frontline in the fight against the virus, but not only this group could experience burnout due to the pandemic.  AIM OF THE STUDY: The aim of this study was to review the most recent available literature on burnout associated with COVID-19. PubMed, SCOPUS, and Google Scholar databases were reviewed. The Phrase "burnout and covid" was used to search the database. Search criteria were: all open access, 2020 and 2021, psychology and English. After Screening titles and abstracts 21 articles were analyzed in detail. RESULTS:  Many studies have shown that healthcare workers experienced burnout. The most vulnerable group were young, female nurses working with COVID-19 patients.  Burnout was also observed among parents, who started working remotely from home or who had to commute to their workplace despite the pandemic. Remote schooling also contributed to burnout among students and teachers. SUMMARY AND CONCLUSIONS: To reduce the possibility of experiencing burnout there are several actions that could be taken. First of all a positive attitude and task oriented actions are helpful in coping in new, stressful situations. Other solutions are social support and psychotherapy.